Zabawa czy afekt? O ideologicznym uwikłaniu twórczości Wiktora Pielewina - Polak, Andrzej (Studia Rossica Posnaniensia, 2022)
The aim of the article is to review Victor Pelevin’s works in terms of their critique of current social and political processes as well as various kinds of ideologies and theories. Despite the writer’s association with the group of postmodern artists he is not only focused on typically postmodern text games and playing with readers, his ambitions are also targeted at shaping their views and behaviors. The author of Generation “P” reacts vividly to the changing reality, he is a keen observer with ambitions to influence the world. He raises issues of universal nature, protesting against all ideological norms, social categories, standardizing fashions and stereotypes that enslave human beings, against all ways of manipulating human consciousness. His approach is constantly met with criticism of both pro-Western and traditionalist circles. The former accuse him of an overly skeptical attitude to the Western model of life, while the latter do not like the writer’s ironic approach to social reality, polemics with Russian values and attempts to discredit them.